The Party’s Explanations in the Civil Court Proceedings - Khatuna Bolkvadze (European Scientific Journal, ESJ, 2017)
According to the Georgian Civil Procedural Code, evidence is information received in legal way, based on which parties protect their rights and legal interests. Physical and juridical persons protect their civil rights in the court. They establish their suit demands on facts which can be proved by means of evidence. So, evidence has great role in the civil process. There are a lot of cases when a party has significant advantage against an opponent, foreseeing material law norms, though his/her suit demand is possible not to be satisfied in the discussion of the case, reasoning not having enough and real evidence, as civil legislation imperatively defines, that each party should prove circumstances on which he/she establishes their demands counterclaim, parties themselves define which facts should be based on their demands or by which evidences these facts should be proved. In the given case, the aim of our research is to study the evidence the party’s explanation, as an evidence in the court practice, is evaluated in the court, how homogeneous the court practice is in relation to this issue and what kind of flaws we have in this aspect.